BLOCKCHAIN-BASED ZERO KNOWLEDGE PROOF MODEL FOR SECURE DATA SHARING SCHEME IN A DISTRIBUTED VEHICULAR NETWORKS - Majigi, Muhammad Umar Majigi; Idris, Ismaila; Abdulhamid, Shafii M.; Uduimoh, Andrew Anogie (FUDMA JOURNAL OF SCIENCES, 2023)
The possibility of implementing advanced applications, such as improved driving safety, has increased with the rapid development of vehicular telematics, and existing vehicular services have been enriched through data sharing and analysis between vehicles. This research uses smart contracts and consortium blockchain zero knowledge proof to secure data sharing and storage in vehicular networks. The results indicate that, for message sizes (m), both data_ experiments _2 and 1 produce ciphertext of the same size 157 bits, with the exception of 'gnfuv-temp-exp1-55d487b85b-5g2xh,' which generates ciphertext of 156 bits with the lowest decryption time of 26,865ms and a small decrease in encryption time between 28,620ms and 28,162ms.  the proposed model validation shows that the model performed better than the Advanced encryption standard in terms of ciphertext size, encryption time and decryption time in comparison and it satisfies the good and robust blockchain-based zero knowledge proof model for secure data sharing and storage for distributed VANET. The scheme achieves high levels of security while operating with reasonable efficiency, reliability and availability according to numerical results.
Keywords: Blockchain; Vehicular Networks; Zero Knowledge Proof; Certificate authority; Roadside units; Data sharing